Analisis Volatilitas Harga Ikan Tuna Di Sentra-Sentra Produksi Di Indonesia Aplikasi Model Arima (Autoregressive Integrated Moving Average) - Ketut Sukiyono; Esla Anggreni Br Ginting; M. Mustopa Romdhon (Jurnal Perikanan Unram, 2024)
One of the marine biological resources in Indonesia is tuna which has a high enough economic value so that tuna can be used as one of the mainstays of non-oil and gas exports from the fisheries sector. The purpose of the study included: analyzing the form of the ARIMA model that most appropriately measures the price volatility of tuna fish in production centers in Indonesia and analyzes the price volatility of tuna fish in production centers in Indonesia. The study used 108 months of time series data from January 2012 to December 2020. In this study, the data analysis method used was ARIMA. The results showed that 1) the best models to measure tuna price volatility are National ARIMA model (3,1,2), Aceh model ARIMA (2,1,2), Bali model ARIMA (1,1,12), North Sulawesi model ARIMA (29,1,29), North Maluku model MA (0,1,2) and West Papua model ARIMA (2,1,1), 2) On the data on tuna prices at the producer level that has been analyzed with the best ARIMA model that the volatility of national tuna prices, Aceh, Bali, North Sulawesi, North Maluku and West Papua are high. The price of tuna in North Maluku cannot be analyzed due to the (0,1,2) moving average model